Kemampuan Penalaran Matematika Ditinjau dari Tipe Kepribadian Siswa SMPN 4 Bukittinggi - Putri, Dea Rahma; Isnaniah, Isnaniah; Imamuddin, M.; Afrinaldi, Afrinaldi (Lembaga Yasin AlSys, 2024)
This study was motivated by observations at SMP Negeri 4 Bukittinggi. As a result of the observation, there were many students in class VIII whose mathematical thinking skills were still low Introverts make decisions carefully, while extroverts make decisions quickly and without much thought, so different people have different ways of thinking. This type of research is described quantitatively. The subjects of this study were students of class VIII.I of SMP Negeri 4 Bukittinggi. The instruments used in this study were essay-style questionnaires and test questions. Based on the research findings, it can be concluded that there are 14 students with extroverted personality type and 13 students with introverted personality type in class VIII.I. Focusing on the extraverted personality type, students' mathematical reasoning skills are classified as low with an average score of 49.5, while students with introverted personality types are classified as medium with an average score of 50,26.